Morpho-functional and psychological profiles of academic athletes in context of athletic training process goals - Namozova, S. S.; Khubbiev, Sh. Z.; Shadrin, L. V.; Ilyina, N. L. (Theory and Practice of Physical Culture, 2017)
The objective of the study was to determine the ways to improve students` sports skills based on their morpho-functional and psychological profiles. The conclusions are: Sports training with due regard to students` psychological profile should include: ??strengthening of relationships between personality characteristics necessary for competitive activities; organization of the training process according to the advances in the modern sports theory and practice; provision of psychological follow-up of sports activities; orientation on elite athletes` personal profiles; formation of the mechanism of achievement of the maximum sports result; consideration of motivation for sports activities, students` expectations from training session and competition; creation of a favorable psychological climate in a sports team and in cooperation with the trainer.